New insights into small molecule activation by acyclic silylenes: a computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Dalton Transactions, 2014)
Recently synthesized acyclic silylenes have the potential to rival transition metal complexes in performing single site small molecule activation, which is significant because of the need to find cheap and green alternatives to transition metal complexes for this important class of reactions. However, the current computational study, a full quantum chemical investigation with density functional theory, demonstrates that undesired side reactions would be competitive in these systems during small molecule activation. The current investigation, in addition to shedding light on this problem, also provides solutions on how the undesired side reactions during small molecule activation can be avoided.